Legal Protection of Patient Privacy Rights in the Use of Electronic Medical Records in Indonesian Hospitals - Masdar, Febriyani; Assam, Rukyyah (Moccasin Journal De Public Perspective, 2026)
The rapid integration of electronic medical records (EMRs) in Indonesian hospitals has improved health care services, but it has also brought up important concerns about privacy protection. This research seeks to assess the effectiveness of legal protection for patient privacy in EMRs by exploring the impact of regulatory awareness, institutional compliance, data governance, and technological measures. This study adopts a quantitative approach based on survey responses from health professionals and administrative personnel responsible for EMRs. Descriptive, reliability, and validity tests, correlation and multiple regression were applied to the data. The results show that all variables have a significant impact on the effectiveness of privacy protection, with data governance practices as the key variable, followed by institutional compliance and technological safeguards but a relatively insignificant effect of regulatory awareness. These findings suggest that the efficacy of legal protection depends on how regulatory principles are institutionalised and technologically implemented. The research suggests a disconnect between the normative and actual legal frameworks, pointing to the importance of holistic governance strategies that incorporate legal, institutional and technological considerations. The results add to the understanding of how to improve data protection in digital health care settings and offer policy insights on how to enhance patient privacy protection in the context of EMRs.